2011
DOI: 10.1051/0004-6361/201117132
|View full text |Cite
|
Sign up to set email alerts
|

The formation of active protoclusters in the Aquila rift: a millimeter continuum view

Abstract: While most stars are believed to form in stellar clusters, the formation and early evolution of young stellar clusters is still largely unknown. Improving our knowledge of the earliest phases of clustered star formation is crucial for understanding the origin of the stellar initial mass function and the efficiency of the star formation process, which both play a key role in the evolution of galaxies. Here, we present an analysis of the Aquila rift complex which addresses the questions of the star formation rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
247
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(266 citation statements)
references
References 69 publications
(136 reference statements)
16
247
3
Order By: Relevance
“…André et al 2010). Core formation is particularly well documented in the case of the B211/B213 filament in Taurus (Schmalzl et al 2010;Onishi et al 2002) or the Serpens South filament in the Aquila Rift (Gutermuth et al 2008;Maury et al 2011).…”
Section: An Evolutionary Scenario For Interstellar Filaments?mentioning
confidence: 98%
“…André et al 2010). Core formation is particularly well documented in the case of the B211/B213 filament in Taurus (Schmalzl et al 2010;Onishi et al 2002) or the Serpens South filament in the Aquila Rift (Gutermuth et al 2008;Maury et al 2011).…”
Section: An Evolutionary Scenario For Interstellar Filaments?mentioning
confidence: 98%
“…This extinction-defined area (see Bontemps et al 2010), rich in gas but initially thought to be almost devoid of star formation (Prato et al 2008), is now known to harbor two cluster-forming clumps (Maury et al 2011): Serpens South, a young protostellar cluster showing very active recent star formation and embedded in a dense filamentary cloud (Gutermuth et al 2008;Bontemps et al 2010;Nakamura et al 2011;Teixeira et al 2012;Friesen et al 2013;Kirk et al 2013a;Tanaka et al 2013), and W40 a young star cluster associated with the eponymous HII region, also known as Sharpless 2-64 (Smith et al 1985;Vallee 1987;Kuhn et al 2010;Pirogov et al 2013).…”
Section: The Aquila Rift Regionmentioning
confidence: 99%
“…Whether or not the southern part of the Aquila highextinction region and the Serpens Main cloud are at the same distance is still a matter of debate Maury et al 2011;Loinard 2013). Based on stellar photometry, Straižys et al (2003) concluded that the front edge of the Aquila molecular cloud was at 255 ± 55 pc.…”
Section: The Aquila Rift Regionmentioning
confidence: 99%
“…1.1 for FHSC lifetimes) or a Class 0 protostar. The prestellar phase lifetime is estimated to be ∼0.5 Myr (Evans et al 2009), and Class 0 objects have estimated lifetimes ranging from ∼4−9 × 10 4 yr (Maury et al 2011) to ∼1.6 × 10 5 yr (Evans et al 2009). Belloche et al (2002) similarly performed radiative transfer modelling of their molecular transitions towards the young Class 0 IRAM 04191 protostar using the MAPYSO code.…”
Section: Infall In Cha-mms1 and In Other Observed Coresmentioning
confidence: 99%